Smart device tracking system using RFID (DeviceTrex) - Norazila, Alias (2010)
Smart Device Tracking Systeifi Using itFIl) (Devicelrax) is a system develops to track the devices at laboratory. The devices that can be track are switches and routers at block X, FSK 11, which are located insIde the Faculty of Computer Systems & Software Engineering (FSKKP) laboratory. Devices are tracking by implement of new technology which is Radio Frequency Identification (RFID). This technology is using Radio Frequency (RF) to transmit signal in order to track the devices. The problem face by !SK Ii laboratory Is the weak security implementation to protect the devices. Admin just use door lock system as a security in this laboratory. Because of the weak security and no special protection for devices inside the laboratory, last year, there is a case where a router is missing. To overcome this problems Device Trax is developing in order to enhance the current security system. The methodology that use in this system is Software Development Life Cycle (SDLC). As we know, SDLC can be divided into five phases which are, planning, analysis, design, implementation, and maintenance. Every phase must be follow step by step in order to being more systematic and well arranged. This system is developing by using RFID passive tag, RFID antenna, RFID reader, and laptop as a host computer for hardware parts. While for software parts, these systems use visual basic.net, and Microsoft Access 2007 for database. The result from this system is, if the RFID tag show red colour, the message box will inform that the device is not found and the admin must take action. This system has successes develop and run smoothly.